가구 형태별 성인 여성의 전자상거래 식품 구매 실태 - 박유진(Yu-Jin Park); 김유미(Yu-Mi Kim); 최미경(Mi-Kyeong Choi) (Korean journal of community nutrition, 2020)
Objectives: The purpose of this study was to compare and analyze e-commerce food purchase behavior and the perceptions of adult women according to their household types. Methods: The e-commerce food purchases of 318 adult women were surveyed and analyzed according to their household types (one-person or couple household (OCH); a household with children (HC); a household with parents (HP)). Results: The total amount of food purchases over 6 months through e-commerce according to household types was in the descending order of OCH (60.3%), HC (57%), and HP (55.1%) thus showing a significant difference (P < 0.05) in behavior between household types. The reasons for purchasing food through e-commerce included: a lower price than offline (30.8%), convenient delivery and transportation (30.2%), and food diversity (21.1%). When purchasing food online, the most important factor was price and quality, followed by quick and accurate delivery for OCH, exact information given about the product for HC, and recommendation from other consumers for HP (P < 0.01). The main foods purchased through e-commerce were coffee, tea (42.1%), instant and frozen foods (39.9%), water, beverages, dairy products (37.7%), snacks, bread, rice cakes (31.5%), and functional foods (27.4%). The percentage of respondents who were very satisfied or satisfied with their e-commerce food purchases was HP (84.1%), OCH (69.9%), and HC (65.6%) in that order (P < 0.05), and 96.5% of all subjects stated that they would be willing to purchase food through e-commerce in the future. The advantages of purchasing food through e-commerce were seen to be the highest in order and payment convenience with 4.1 points out of 5, followed by low price (4.0), variety of products (3.9), and ease of food purchase (3.9). Among the disadvantages listed, concerns about product damage and deterioration during delivery and differences between the displayed product and the delivered product were the highest with 3.7 points. Conclusions: The characteristics and perceptions of female consumers according to household types are important factors in enhancing the reach of e-commerce, and in preparing guidelines for food selection through e-commerce.